A review on patient-specific facial and cranial implant design using Artificial Intelligence (AI) techniques. (3rd October 2021) - Memon, Afaque Rafique; Li, Jianning; Egger, Jan; Chen, Xiaojun
ABSTRACT: Introduction: Researchers and engineers have found their importance in healthcare industry including recent updates in patient-specific implant (PSI) design. CAD/CAM technology plays an important role in the design and development of Artificial Intelligence (AI) based implants. The across the globe have their interest focused on the design and manufacturing of AI-based implants in everyday professional use can decrease the cost, improve patient's health and increase efficiency, and thus many implant designers and manufacturers practice. Areas covered: The focus of this study has been to manufacture smart devices that can make contact with the world as normal people do, understand their language, and learn to improve from real-life examples. Machine learning can be guided using a heavy amount of data sets and algorithms that can improve its ability to learn to perform the task. In this review, artificial intelligence (AI), deep learning, and machine-learning techniques are studied in the design of biomedical implants. Expert opinion: The main purpose of this article was to highlight important AI techniques to design PSIs. These are the automatic techniques to help designers to design patient-specific implants using AI algorithms such as deep learning, machine learning, and some other automatic methods.